Humanitarian Negotiations with Armed Groups The Frontlines of Diplomacy. - Clements, Ashley (Ashley Jonathan) (Milton : Routledge, 2019)
Humanitarians operate on the frontlines of today's armed conflicts, where they regularly negotiate to provide assistance and to protect vulnerable civilians. This book explores this unique and under-researched field of humanitarian negotiation. It details the challenges faced by humanitarians negotiating with armed groups in Yemen, Myanmar, and elsewhere, arguing that humanitarians typically negotiate from a position of weakness. It also explores some of the tactics and strategies they use to overcome this power asymmetry to reach more favorable agreements. The author applies these findings to broader negotiation scholarship and investigates the implications of this research for the field and practice of humanitarianism. This book also demonstrates how non-state actors - both humanitarians and armed groups - have become increasingly potent diplomatic actors. It challenges traditional state-centric approaches to diplomacy and argues that non-state actors constitute an increasingly crucial vector through which international relations are replicated and reconstituted during contemporary armed conflict. Only by accepting these changes to the nature of diplomacy itself can the causes, symptoms, and solutions to armed conflict be better managed. This book will be of interest to scholars concerned with conflict resolution, negotiation, and mediation, as well as to humanitarian practitioners themselves.
4 Overcoming power asymmetryTactical options for the weak; Deploying humanitarian levers; The promise of humanitarian diplomacy; Conclusion; 5 Advancing the frontlines of humanitarian negotiation; Conceptual boundaries; Paradoxes; Implications for theory and practice; Next steps: a research agenda; Conclusion; 6 Conclusion; Appendix 1 Glossary of access terms; Selected bibliography; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: POLITICAL SCIENCE / General; Diplomatic negotiations in international disputes -- Handbooks, manuals, etc; Humanitarian assistance -- Handbooks, manuals, etc